2008
DOI: 10.1093/humrep/den338
|View full text |Cite
|
Sign up to set email alerts
|

British women's attitudes to surrogacy

Abstract: Further research is needed with larger sample sizes of potential surrogates to determine whether the predictive attitudes reported here translate to actual behaviours. The larger group which was not interested in considering becoming a surrogate scored significantly more negatively on all attitudes towards surrogacy. The negative attitudes reported by the 'unwilling to consider being a surrogate' group may reflect attitudes held by the majority of the population and are likely to be influenced by reports of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 29 publications
1
35
1
8
Order By: Relevance
“…Also another study revealed that these intentions were the most important aspects of future desire for surrogacy in women (22). 2 participants were divorced and others (3 participants) were married.…”
Section: Discussionmentioning
confidence: 98%
“…Also another study revealed that these intentions were the most important aspects of future desire for surrogacy in women (22). 2 participants were divorced and others (3 participants) were married.…”
Section: Discussionmentioning
confidence: 98%
“…Attitudes toward surrogacy have been reported to be less positive than attitudes toward gamete donation (Chliaoutakis, 2002; Suzuki et al, 2006), with traditional surrogacy being seen as posing the most serious ethical concerns (Shreffler et al, 2010). Only a few women have reported being willing to become surrogates themselves, but it is unclear whether their reluctance is related to ethical concerns or something else (Poote and Van den Akker, 2009). Ethical concerns were greater at Wave 1 for technologies that entailed the involvement of a third party than for technologies that did not entail such involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Attitude surveys have demonstrated that surrogacy is the least acceptable method of family building (Dunn et al, 1988;Halman et al, 1992;Genius et al, 1993); non-commercial altruistic surrogacy is more acceptable than commercial surrogacy (Krishnan, 1994), and religion affects acceptability of surrogacy (Chliaoutakis et al, 2002;Dempsey and Critchley, 2010). Partial surrogacy is also perceived as less acceptable than full surrogacy (Appleton, 1990;Bromham, 1991;Frazier and Chapman, 1994;BMA, 1996;Suzuki et al, 2006;Poote and van den Akker, 2009), although more recent research has shown attitudes to be more variable (Dempsey and Critchley, 2010;Constantinidis and Cook, 2012). The attitudes are likely to be influenced by media reports of controversial, negative, or illegal surrogate practices (Appleton, 2001).…”
mentioning
confidence: 99%